Pengembangan Sistem Informasi Tiket Pelanggan Berbasis Web Menggunakan Metode Prototype dan Evaluasi Kualitas Berdasarkan Standar Iso/Iec 25010 - Dheo Dermawan; Multiana Multiana; Chairul Anwar (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
The rapid development of information technology in the era of digital transformation has significantly changed various aspects of organizational operations. PT Teknologi Informatika Solusindo, a company engaged in information technology services and customer service management, faces challenges in managing customer tickets that are still carried out manually, resulting in data recording delays, duplication, and lack of transparency in ticket resolution status. This research aims to analyze existing system problems, design and build a web-based customer ticket information system using the Prototype method, and evaluate system quality based on the ISO/IEC 25010 standard. The research used a mixed-method approach combining qualitative and quantitative methods. Data collection was carried out through observation, interviews, literature study, and documentation. System development used the Prototype method which includes planning, design, development, testing, and iteration stages. The system was modeled using UML, including use case, activity, sequence, and class diagrams. Quality testing using ISO/IEC 25010 covers aspects of Functional Suitability, Performance Efficiency, Usability, Reliability, Security, Compatibility, maintainability, and Portability. The results show that the developed system is able to improve the effectiveness and efficiency of customer ticket management, provide real-time monitoring, and produce service reports automatically. Quality evaluation results indicate that the system meets user needs and is feasible to implement in the company.